2006
DOI: 10.1111/j.1399-3054.2006.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron excess on cell viability and mitogen‐activated protein kinase activation in rice roots

Abstract: Iron is an essential micronutrient for normal growth and development of plants. However, at high concentrations, iron can become toxic to plants. Very little information is known about the molecular mechanism responsible for the regulation of plant growth by excess iron. The aim of this study was to investigate the signal transduction pathway activated by increasing concentrations (0.5, 1.0, and 2.5 mm) of iron. We showed that iron elicited a remarkable myelin basic protein (MBP) kinase activity. By Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The iron content and concentration of roots and seeds increased significantly in Zn-deficient plants. This may intensify the stressful conditions on plant through the induction of ROS production (Tsai and Huang 2006). The iron uptake in rice competes with Zn uptake as it is carried out by similar metal transporters (ZIP transporters) (Masuda et al 2012).…”
Section: Effect Of Zn Supplymentioning
confidence: 99%
“…The iron content and concentration of roots and seeds increased significantly in Zn-deficient plants. This may intensify the stressful conditions on plant through the induction of ROS production (Tsai and Huang 2006). The iron uptake in rice competes with Zn uptake as it is carried out by similar metal transporters (ZIP transporters) (Masuda et al 2012).…”
Section: Effect Of Zn Supplymentioning
confidence: 99%
“…Although iron is a vital micronutrient for plant growth and development (Connolly et al 2003;Connolly and Guerinot 2002), its high content in the substrate can affect cellular homeostasis and cause toxic effects (Williams et al 2000;Ducic and Polle 2005) like oxidative stress in cells, which may result in tissue damage (Becana et al 1998;Tsai and Huang 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, Zhang and Liu (2001) demonstrated that increases of salicylate-induced protein kinase (SIPK) activity alone induce defense gene activation and cell death in tobacco. Previously, it was also found that Cd, Cu, Zn, and Fe could activate MAPKs phosphorylation in rice and alfalfa plants (Yeh et al 2003(Yeh et al , 2007Jonak et al 2004;Lin et al 2005;Tsai and Huang 2006). Moreover, the Cu-induced MAP kinase activation required the involvement of NADPH oxidases, Ca 2+ -dependent protein kinase (CDPK) and phosphatidylinositol 3-kinase (PI3 kinase).…”
Section: Discussionmentioning
confidence: 96%